If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + -1) + y = 2y + 20 Reorder the terms: 4(-1 + y) + y = 2y + 20 (-1 * 4 + y * 4) + y = 2y + 20 (-4 + 4y) + y = 2y + 20 Combine like terms: 4y + y = 5y -4 + 5y = 2y + 20 Reorder the terms: -4 + 5y = 20 + 2y Solving -4 + 5y = 20 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -4 + 5y + -2y = 20 + 2y + -2y Combine like terms: 5y + -2y = 3y -4 + 3y = 20 + 2y + -2y Combine like terms: 2y + -2y = 0 -4 + 3y = 20 + 0 -4 + 3y = 20 Add '4' to each side of the equation. -4 + 4 + 3y = 20 + 4 Combine like terms: -4 + 4 = 0 0 + 3y = 20 + 4 3y = 20 + 4 Combine like terms: 20 + 4 = 24 3y = 24 Divide each side by '3'. y = 8 Simplifying y = 8
| 42x+42=42x+42 | | 3+5u=98 | | 4(y+5)-24=0 | | 5(x+8)-9= | | 6(T+2)+3(3-5T)=10(T-4)-6 | | 11x+9=8x | | 15=5x-3 | | x^2+9x-21=0 | | 7x-6-3x=10 | | -3(x-2)=-15 | | -6(3x*-8)= | | 12x^2+2x-4=o | | 7(3k+4)-18k=64 | | 6=.5m-5 | | 15(b+2)=90 | | -6(3*-8)= | | -12+9=m-2 | | 2x^2+3x-36=0 | | 2k-8=13+5k | | 5z+9=3z-1 | | x-.3x=50 | | 10d=-34-5d | | x-16=25 | | 2v+18=6-4(v-17) | | 19.5+0.5=10.6206-0.4t | | 24-5*3/8-5= | | -13=-4(4)+3 | | 5x+9=3z-1 | | -4+6(8X+2)=296 | | 121x^4-81=0 | | 7+2(6)= | | -3(9r+4)= |